Numerical Analysis of Precast Rubberized Lightweight Concrete Wall Panel - Lai, Jin Ming (2021)
Precast concrete wall panels are common prefabricated building components used to replace conventional burnt clay bricks as non-load bearing walls. Recent researches focused on lightweight concrete wall panel due to its low density which would lead to the reduction in total building load. This research aimed to evaluate the engineering properties of precast rubberized lightweight concrete wall panel subjected to compressive loading through numerical analysis software, ABAQUS. Concrete smeared cracking was used to model the behaviour of concrete. A comparative study was conducted to examine the differences between the control sample and rubberized concrete wall panel under compressive strength. Next, separate rubberized concrete wall panel with calcium silicate board and concrete capping were modelled to evaluate the confining effect. Lastly, a combined wall panel was modelled, which comprises three single rubberized concrete wall panels to assess its actual behaviour in real-life practice. At 7.5 % crumb rubber replacement, the ultimate compressive strength reduced by 13 %, followed by an improvement in ultimate strain by 5 %. Both concrete capping and calcium silicate board did not cause any significant impact on the ultimate compressive strength but drop in ultimate strain by 11 % and 5 %, respectively. The numerical results underlined that the ultimate strain for the combined rubberized concrete wall panel had significantly improved from 0.0018 to 0.0027. Further research could be carried out with a higher crumb rubber replacement rate and different slenderness ratio.